Features and content of gender education of women-leaders in the activities of non-governmental organizations and movements - O.А. Bolotska (Academy of Cognitive and Natural Sciences, 2006)
The paragraph и dedicate io the actual problem of introducing Gender's education in the Pedagogical and theoretical analysis of the specific nature Gender's upbringing women leader in the activity social organizations and movements.